THE RELATIONSHIP OF BULIAN WOOD THICKNESS TO FILM DENSITY AS THE ABSORPTION CAPABILITY OF BULIAN WOOD TOWARDS RADIATIONMAMPUAN SERAPAN KAYU BULIAN TERHADAP RADIASI: ANALYSIS OF IRONWOOD THICKNESS ON FILM DENSITY AS THE ABSORPTION CAPACITY OF IRONWOOD AGAINST RADIATION - Sari, Oktavia Puspita (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2025)
In Indonesian, many natural materials actually have the potential to become radiation-blocking, including Bulian wood. For this reason, it is necessary to conduct research on the absorption capacity of Bulianwood, which has the potential to be used as a radiation barrier. This research aims to determine the absorption capacity of Bulian wood thickness, which is equivalent to 2 mm Pb, using experimental methods. Thus, research was conducted in the laboratory of the radiology program study at Baiturrahmah University. The sample is the form of film density at each level of the step wedge with Bulian wood and timber with a thickness of 2 mm. The data was processed with bivariate analysis. The result with the correlation test is the value of p = 0.00, so Ho rejected and ha is accepted so a significant relationship is obtained between the thicknes of 25 mm Wood Buliain and 2 mm PB